2009
DOI: 10.1029/2009gl039663
|View full text |Cite
|
Sign up to set email alerts
|

Sources and fate of freshwater exported in the East Greenland Current

Abstract: Monitoring the sources and fate of freshwater in the East Greenland Current (EGC) is important, as this water has the potential to suppress deep convection in the Nordic and Labrador Seas if the outflow of freshwater from the Arctic Ocean increases in response to climate change. Here, hydrographic, oxygen isotope ratio and dissolved barium concentration sections across Denmark Strait collected in 1998 and 1999 are used to determine the freshwater composition of the EGC at these times. Comparison of meltwater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 21 publications
4
69
1
Order By: Relevance
“…5) is about 2:1 in all of our surveys, except 1998. Previous studies have found that a similar ratio of MW to FIFB is generally observed in station or section inventories (Meredith et al, 2001;Dodd et al, 2009;Rabe et al, 2009) and section transports (Rabe et al, 2009). This has been attributed to processes in the Arctic Ocean "upstream" from the Arctic outflow in the Fram Strait.…”
Section: Covariability Of Different Lfw Componentsmentioning
confidence: 84%
See 3 more Smart Citations
“…5) is about 2:1 in all of our surveys, except 1998. Previous studies have found that a similar ratio of MW to FIFB is generally observed in station or section inventories (Meredith et al, 2001;Dodd et al, 2009;Rabe et al, 2009) and section transports (Rabe et al, 2009). This has been attributed to processes in the Arctic Ocean "upstream" from the Arctic outflow in the Fram Strait.…”
Section: Covariability Of Different Lfw Componentsmentioning
confidence: 84%
“…This method uses a system of linear equations (endmember balance) to derive the aforementioned water mass fractions and fractions of Atlantic Water (AW) from each observed tracer, assuming certain end-member values for each tracer (see also Ekwurzel et al, 2001;Jones et al, 2008a;Yamamoto-Kawai et al, 2008). In addition to further years of observations, the main difference to previous work (Dodd et al, 2009;Rabe et al, 2009) is the inclusion of nitrate and phosphate observations to distinguish PW in the end-member balance. δ 18 O for the SIM end-member was set to a constant value, rather than relating it to the surface value of each profile.…”
Section: Velocity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…An approximately constant ratio between inventories of f i and f r has been observed before, e.g. in the region of export of Arctic Ocean halocline waters within the western Fram Strait areas (Dodd et al, 2009;Rabe et al, 2009;Meredith et al, 2001;Bauch et al, 1995) The whole 2007 dataset from the Eurasian and Makarov basins shows a wide range of f i to f r ratios, which depend on salinity and corresponding depth level within the halocline (Fig. 9), and on the regional origin too (Fig.…”
Section: Correlation Between F R and F Imentioning
confidence: 99%